Recent Publications (Quarterly Journal of Economics, 1951)
Journal Article Recent Publications Get access The Quarterly Journal of Economics, Volume 65, Issue 2, May 1951, Pages 290–291, https://doi.org/10.1093/qje/65.2.290 Published: 01 May 1951